Bud burst induction in BRS-Carmem vine minicuttings under controlled environment - Tainá Machado Ribeiro, Luana; Binotto, Carolina; Danilo Shimizu, Gabriel; Tiaki Higuchi, Maíra; Ruffo Roberto, Sergio; Jefferson Sato, Alessandro (Comunicata Scientiae, 2021)
A search for new products and alternative techniques to artificially overcome the dormancy of temperate climate plants has increased. Thus, the present work aimed to evaluate the efficiency of the application of vegetable oil, mineral oil, garlic extract and hydrogenated cyanamide on budburst of ‘BRS Carmem’ vine under controlled environment (B.O.D). The randomized design arranged in a 2 × 6 factorial scheme was used as a statistical model, with four repetitions with nine minicuttings per plot. The first factor consisted of the exposure or not of the minicuttings to 400 hrs of cold (<7.2 ºC), and the second factor was composed by the alternative tests: control; mineral oil (MO), vegetable oil (VO); MO + VO, hydrogenated cyanamide; and garlic extract. The bud swell and sprouting formation at 20 days after the application were evaluated, and the average time and speed index of bud swell, and the average time and speed index of sprouting were calculated. For minicuttings not exposed to the cold, the best results in terms of bud swell and sprouting was observed with the application of MO, followed by the application of hydrogenated cyanamide. For minicuttings exposed to 400 hrs, the best results regarding bud swell and sprouting was observed with the application of the oils association. It can be concluded that the best results for sprouting were obtained when minicuttings were not exposed to cold with an application of the association of MO and VO.